Temporal progress of Septoria leaf spot on rabbiteye blueberry (Vaccinium ashei) - Ojiambo, P.; Scherm, H. (Scientific Societies, 2005)
Septoria leaf spot, caused by Septoria albopunctata, is an important disease on blueberry in the southeastern United States, yet its epidemiology is largely unknown. Disease severity and dissemination of pycnidiospores were monitored from 2002 to 2004 in a planting of susceptible Premier rabbiteye blueberry to characterize the temporal progress of the disease and determine the effect of inoculum dynamics and selected leaf attributes on disease development. Disease onset was observed between late April and mid-June, followed by a rapid increase in disease severity until mid- to late September; thereafter, disease severity decreased until the end of the season due to abscission of severely infected leaves. A logistic model was fitted to disease severity data using nonlinear regression, and parameter estimates were used to compare the effects of leaf position on the shoot and shoot location in the canopy on disease progress. Based on this model, the highest absolute rate of disease increase and the highest upper asymptote of disease severity were predicted for leaves in intermediate positions on the shoot and for shoots in the lower canopy. Data collected with funnel spore samplers showed that splash-dispersed pycnidiospores of S. albopunctata were available throughout most of the period from April through late October. Final disease severity on individual leaves was more strongly correlated with cumulative spore numbers throughout the entire season (from leaf emergence to the end of the assessment period in November) than with cumulative spore numbers during shorter periods around the time of leaf emergence; this suggests that infection is not limited to young, expanding leaves, but rather that leaves at all developmental stages can become infected by S. albopunctata seasonlong. Disease incidence on leaves of potted trap plants exposed to natural inoculum in the field during rain events in 2003 and 2004 was >70.0% irrespective of leaf developmental stage at the time of exposure. Taken together, the results of this study indicate that inoculum of S. albopunctata is present throughout most of the growing season and that infection can occur season-long on leaves of any age, giving rise to a polycyclic epidemic.